DESKRIPSI KEMAMPUAN KONEKSI MATEMATIS SISWA SMP PADA MATERI SEGITIGA DAN SEGIEMPAT - Lia Tresnawati; Indrie Noor Aini (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Students need to have mathematical abilities when study mathematics, one of which is mathematical connection. The purpose of this research is to describe the mastery of junior high school students in the ability of mathematical connection with triangle and quadrilateral material. Descriptive qualitative method was chosen in this study. Research is carried out in an even semester in the 2020-2021 school year, which is located in one of the public junior high schools in Karawang Regency. A total of 6 students of class VII were used as research subjects. The research instrument was in the form of 3 test questions of mathematical connection ability in the form of a description. Based on the exposure of the research results, the average percentage of mathematical connection ability achievement is 38%. Thus, it was concluded that the mastery of the mathematical connection ability of junior high school students in the triangle and quadrilateral material was in the low category.